Membuat Animasi 2D menggunakan Java NetBeans : Animasi 2D - Asep Awaludin, Asep; Izra Rafif Rabbani, Izra; Perwira Syahida Rahman, Perwira; Sri Ghantika Maharani, Sri; Ines Heidiani Iksari, Ines (Jurnal Riset Informatika dan Inovasi, 2024)
This study examines the creation of 2D animations using Java NetBeans. In this research, classes such as "Graphics2D" and "Timer" are utilized to control the animation. Findings indicate that Java NetBeans is a robust and flexible platform for 2D animation development, despite challenges in optimizing complex animations and integrating GUI elements. In conclusion, Java NetBeans proves effective for 2D animations and beneficial for game development, data visualization, and interactive interface design.